2021
DOI: 10.3390/s21082626
|View full text |Cite
|
Sign up to set email alerts
|

Platoon Merging Approach Based on Hybrid Trajectory Planning and CACC Strategies

Abstract: Currently, the increase of transport demands along with the limited capacity of the road network have increased traffic congestion in urban and highway scenarios. Technologies such as Cooperative Adaptive Cruise Control (CACC) emerge as efficient solutions. However, a higher level of cooperation among multiple vehicle platoons is needed to improve, effectively, the traffic flow. In this paper, a global solution to merge two platoons is presented. This approach combines: (i) a longitudinal controller based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, a balance between accuracy and complexity should be struck. The first two points affect the parameters in Equations ( 2) and ( 4)- (6). There are specific patterns of change over a short period of time.…”
Section: Vehicle Longitudinal Dynamics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a balance between accuracy and complexity should be struck. The first two points affect the parameters in Equations ( 2) and ( 4)- (6). There are specific patterns of change over a short period of time.…”
Section: Vehicle Longitudinal Dynamics Modelmentioning
confidence: 99%
“…Nevertheless, conventional ACC systems have limitations in terms of energy efficiency, driver comfort, and tracking stability. To address these challenges, researchers have proposed various ACC extensions, including cooperative adaptive cruise control (CACC) [6][7][8], personalized adaptive cruise control (PACC) [9][10][11], and energy-optimal adaptive cruise control (EACC) [1,[12][13][14][15]. CACC enables multi-vehicle cooperation through vehicle communication systems, while PACC tailor sand simulates individual driving habits.…”
Section: Introductionmentioning
confidence: 99%
“…From literature reviews, much research has been conducted on mixed traffic flow modeling to study its characteristics under normal weather conditions. Some studies focused on the headway of the CAVs during the car-following process to describe the longitudinal dynamics of the mixed traffic [7][8][9]. Some studies focused on the possible impact of autonomous vehicles on traffic flow and found that the traffic throughput increases at a high CAV penetration rate [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in different industrial applications, the end effector is utilized by the robot manipulator to permit via the preferred curve to avoid collision with an obstacle in the robot environment (Qian et al, 2020). This issue is most challenging, still, scholars have established particular comparatively efficient solutions (Hidalgo et al, 2021; Liu et al, 2019). Moreover, in robotic applications like painting, welding, and part assembly, online procedures for continuous paths or tracking control can be found (Reiter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%